Advancing musculoskeletal shoulder modeling: reflecting glenohumeral translation with bony, ligamentous, and muscular stability constraints - Menze, Johanna; Croci, Eleonora; Andersen, Michael Skipper; Hess, Hanspeter; Lund, Morten Enemark; De Pieri, Enrico; Zumstein, Matthias A.; Ferguson, Stephen J.; Müller, Andreas Marc; Mündermann, Annegret; Gerber, Kate (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionGlenohumeral (GH) stability is a delicate interplay between bony congruence, muscle contraction, and ligamentous or capsular stability that can be disrupted by pathologies such as rotator cuff (RC) tears. We aimed to develop an advanced musculoskeletal shoulder model that incorporates subject-specific GH joint contact, active and passive muscle stability, and mechanical properties of ligaments to calculate GH translation using force-dependent kinematics (FDK). We hypothesized that inferior-superior GH translation computed using this model are consistent with in vivo GH translation measured by dynamic uniplanar fluoroscopy in healthy shoulders and in shoulders with partial or full RC tears, and that muscle and joint forces computed using the FDK shoulder model are higher than those of the default shoulder model.MethodsThe AnyBody ShoulderArm model was extended to compute GH translation using FDK, considering joint constraints due to bone congruence and to labrum, ligament and muscle stabilization. The inferior-superior GH translations computed using the FDK model were compared with the translations measured using dynamic uniplanar fluoroscopy in healthy shoulders and shoulders with partial and full RC tears during 0°–30° abduction-adduction cycles with 0–3 kg of handheld weight.ResultsThe FDK model simulations revealed a decrease in median inferior-superior translations, from 2.8 to 1.8 mm with increasing handheld weight (0–3 kg) which was higher than those observed in fluoroscopic imaging (1.4 mm and 1.1 mm at 0 and 2 kg handheld weight). FDK model simulations in abduction with no additional handheld weight revealed greater variations in glenohumeral translations in shoulders with full RC tear. Compressive joint forces and muscle forces were higher in the FDK model than in the default shoulder model, particularly in the infraspinatus in the healthy model and in the deltoid in the full RC tear model.DiscussionDistinct differences in muscle and joint forces between the FDK and the default shoulder models confirm that unconstrained translational degrees of freedom of the GH joint are important to advance knowledge of the biomechanical principles of the shoulder. Computed inferior-superior GH translations were greater than in vivo measured GH translations, suggesting that joint stability, particularly through muscle recruitment, could be underestimated.